(untitled) (International relations and international law Journal, 2023)
Transport corridors, often referred to as the "lifeblood" of the contemporary economy; wield considerable influence in facilitating the unimpeded flow of goods, people, and ideas. Nevertheless, a pressing inquiry has emerged in recent times: could these infrastructures, crafted to enhance economic interconnectedness, impose significant harm on the delicate environmental ecosystem? As nations progressively endeavor to enlarge and modernize their infrastructure to bolster economic advancement, the discourse regarding the potential detriment posed by the construction and expansion of transport corridors to the environment intensifies. This article delves into diverse facets of the adverse repercussions of transport corridors on the environment. A paramount outcome of the evolution of these corridors is the degradation of the natural surroundings. Whether they are highways, railways, or pipelines, many necessitate extensive land clearing, leading to the felling of forests and the disruption of wetlands and grazing lands. These ecosystems serve as habitats for a myriad of plant and animal species, and their degradation could precipitate the loss of biodiversity, the extinction of species, and the disturbance of the delicate equilibrium within ecosystems. It is crucial to underscore that the loss of habitat attributable to the construction of transport corridors poses a peril not solely to individual species but also to the entire ecosystem. This could instigate disruptions in the food chain, alterations in migratory patterns, and even the impending extinction of several species. Consequently, this article poses the question of how to strike a balance between the expansion of transport corridors and the preservation of nature. Additionally, it explores strategies to implement that advocate for the sustainable utilization of these pivotal economic conduits. Keywords: transport routes, ecologization, nature, geo-economics, and environmental standards.